EXPERIENCE OF PROJECT-BASED LEARNING: AN ATTEMPT AT OBJECTIVE ANALYSIS OF RESULTS AND PROBLEMS - D. A. Trishchenko (Образование и наука, 2018)
Introduction. The method of project-based learning has recently gained the great popularity. However, the adoption of project-based learning into the educational process and its theoretical comprehension have been affected to some extent by a phenomenon such as fashion, therefore, there has been misunderstanding on the part of this method potential among the research and teaching staff. The possible disappointment in its results, where there are reasons to doubt its effectiveness, can cause a backlash and retard its application. The reassessment of its results, in turn, can cause a backlash and retard its methodological and methodical tools application that has a really high potential. The aims of the study are the following: to define and analyse insufficiently highlighted problematic aspects of the project-based learning in scientific publications; to justify the need for a differentiated approach to its use. Methodology and research methods. The study methodology is based on the system-based and practice-oriented approaches; the methods of experiment, description, comparison, structural and comparative analyses of empirical data were applied. Results and scientific novelty. The author describes the long-term teaching experience based on the project method while training the students of the system of higher and secondary professional education mastering the technologies of a promotional video production. The virtues and shortcomings of this method, favorable conditions for its realization are considered; a number of the methodical recommendations that enable to increase its effectiveness are given; typical mistakes which are made when introducing similar training are noted. The use of the project method brings closer the process of the specialists’ training to real professional activity; removes a problem of restriction of school hours; gives opportunities of peer learning of students and acquisition of the program of courses by them at individual speed; significantly stimulates educational motivation of students and promotes growth of their professional competence through the well-advised organization of work on the project, its constant control and objective assessment by independent experts of a final design product. The use of the project-based learning method is not universally effective. It contributes more to the development of the abilities of more gifted students, but can negatively affect the progress of poorly motivated students. Projects can be realized within the framework of one studied discipline, if its content and structure create conditions for this. In other cases, it will require a substantial restructuring of the educational process, careful prediction of its final results, change of approaches to teaching all disciplines, and accordance of the educational curricula to design technologies. Practical significance. The publication materials can be used by the teachers, methodologists and administrative workers of the system of professional education interested in the efficient and rational organization of educational process and the choice of the most productive methods, means and forms of vocational training of future experts.